Complete primary repair of bladder exstrophy: a systematic review. Issue 2 (April 2020) - Pathak, Piyush; Ring, Joshua D.; Delfino, Kristin R.; Dynda, Danuda I.; Mathews, Ranjiv I.
Summary: Objectives: Complete primary repair of exstrophy (CPRE) was established as a method to reduce numbers of procedures for the reconstruction of bladder exstrophy (BE). Performed since 1989, some suggest it as a replacement for the staged reconstructive procedure, the gold standard. Does CPRE reduce the numbers of procedures for reconstruction of BE? Methods: Literature was reviewed from 1989 to 2016, and articles evaluating outcomes of patients undergoing CPRE, extracted. Effort was made to obtain final data from each reporting institution/group. Eleven articles meeting criteria were evaluated for qualitative systematic review. Age at initial closure, complications, additional procedures, and outcomes were evaluated to provide an overview of CPRE. Results: Ten groups reported BE management using the CPRE technique. 236 patients (153 boys; 72 girls; 11 unknown sex) had primary closure ranging from birth to 5.6 years. Osteotomy was favored by most in infants closed beyond the first 72 h of life along with spica cast immobilization. Three groups recommended concomitant augmentation for infants with small bladder capacities. Ureteral reimplantation was required in 58 patients with recurrent urinary tract infections resistant to prophylaxis. Hypospadias repair was required for most boys having complete penile disassembly, and most children eventually required bladder neck reconstruction (BNR) for continence. Overall, voiding without BNR was noted in 16–37% of children in the reported series. Conclusions: Complete primary repair of exstrophy has been suggested as a single procedure for the management of BE. Literature review suggests most patients require multiple procedures to complete reconstruction and attain continence.